2022
DOI: 10.3389/fneur.2022.816243
|View full text |Cite
|
Sign up to set email alerts
|

Clinical Predictors of Relapse in a Cohort of Steroid-Treated Patients With Well-Controlled Myasthenia Gravis

Abstract: ObjectiveDespite the high efficiency of glucocorticoids (GCs), ~18–34% patients with myasthenia gravis (MG) may experience relapses of the disease. Here, we aim to identify clinical factors related to relapses during steroid tapering or after withdrawal in MG patients who were well-managed on steroid monotherapy.MethodsWe conducted a retrospective study on 125 MG patients from the Xuanwu Hospital MG Trial Database. Patients were treated with corticosteroids and achieved minimal manifestation status (MMS) or be… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
2
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 30 publications
2
2
1
Order By: Relevance
“…Similar to other studies, most exacerbations (58.9%) occurred within the first 2 years of remission status being achieved ( 12 , 14 ). The MGFA classification was identified as an independent contributor to GMG relapse, suggesting that more severe clinical symptoms tend to be associated with a higher risk of exacerbation ( 14 ). We also found, in contrast to a previous study, that gender showed noassociation with exacerbation ( 2 ).…”
Section: Discussionsupporting
confidence: 89%
See 2 more Smart Citations
“…Similar to other studies, most exacerbations (58.9%) occurred within the first 2 years of remission status being achieved ( 12 , 14 ). The MGFA classification was identified as an independent contributor to GMG relapse, suggesting that more severe clinical symptoms tend to be associated with a higher risk of exacerbation ( 14 ). We also found, in contrast to a previous study, that gender showed noassociation with exacerbation ( 2 ).…”
Section: Discussionsupporting
confidence: 89%
“…exhibiting GMG after disease onset. The results indicated that nearly 69.1% of adults with GMG experienced exacerbations, higher than the 33.7%-60.6% reported in previous literature, which may be related to higher severity and longer follow-up periods in the patients enrolled in our study (9,(12)(13)(14). Similar to other studies, most exacerbations (58.9%) occurred within the first 2 years of remission status being achieved (12,14).…”
Section: Discussionsupporting
confidence: 73%
See 1 more Smart Citation
“…16 However, these studies mainly focused on specific subtypes, for example, anti-AChR antibody-positive generalized MG; or pre-defined conditions, for example, well-controlled patients treated with steroids, and were not suitable for a consecutive follow-up setting. 17,18 In the current study, we aimed to develop and validate a data-driven, machine learning (ML)based, predictive model to forecast the short-term outcome for MG. The advantages of this model include (1) accommodating three subtypes of MG (AChR, MuSK, negative); (2) being robust and replicable; (3) feasible for health professional evaluations.…”
Section: Short-term Outcome Prediction For Myasthenia Gravis: An Expl...mentioning
confidence: 99%
“… 16 However, these studies mainly focused on specific subtypes, for example, anti-AChR antibody-positive generalized MG; or pre-defined conditions, for example, well-controlled patients treated with steroids, and were not suitable for a consecutive follow-up setting. 17 , 18 …”
Section: Introductionmentioning
confidence: 99%